MULTICOMPLICATED MYOCARDIAL INFARCTION - Babiy, O. G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
The clinical course of myocardial infarction frequently burdened by a variety of complications, which largely determine its scenario and prognosis. Despite advances in the management of this disease, complications can and do occur. These dangers arise from two principal sources: on the one hand, from the local effects of the lesion and the circulatory depression that follows, and, on the other, from the hazards that may attend during active treatment. On example of clinical case is demonstrated severe course of myocardial infarction with development of multiple complications at different stages, but, ultimately, with a favorable outcome. Early, aggressive, and judicious treatment of these complications may substantially decrease the morbidity and mortality associated with this disease.